The Cambridge introduction to modern British fiction, 1950-2000 - Head, Dominic (Cambridge University, 2013)
In this introduction to post-war fiction in Britain, Dominic Head shows how the novel yields a special insight into the important areas of social and cultural history in the second half of the twentieth century. Head's study is the most exhaustive survey of post-war British fiction available. It includes chapters on the state and the novel, class and social change, gender and sexual identity, national identity and multiculturalism. Throughout Head places novels in their social and historical context. He highlights the emergence and prominence of particular genres and links these developments to the wider cultural context. He also provides provocative readings of important individual novelists, particularly those who remain staple reference points in the study of the subject. Accessible, wide-ranging and designed specifically for use on courses, this is the most current introduction to the subject available.